Chronic HIV-1 Infection Induces B-Cell Dysfunction That Is Incompletely Resolved by Long-Term Antiretroviral Therapy. (1st April 2016) - Abudulai, Laila N.; Fernandez, Sonia; Corscadden, Karli; Hunter, Michael; Kirkham, Lea-Ann S.; Post, Jeffrey J.; French, Martyn A.
Abstract : Objectives: To determine the effect of long-term antiretroviral therapy (ART) on HIV-1–induced B-cell dysfunction. Design: Comparative study of ART-naive and ART-treated HIV-infected patients with non-HIV controls. Methods: B-cell dysfunction was examined in patients with HIV-1 infection (n = 30) who had received ART for a median time of 9.25 years (range: 1.3–21.7) by assessing proportions of CD21 lo/- B cells (a marker of B-cell exhaustion) and proportions of tumor necrosis factor-related apoptosis-inducing ligand + or B and T lymphocyte attenuator + B cells, and serum levels of immunoglobulin free light chains (markers of B-cell hyperactivation). The association of these markers with serum levels of IgG1 and IgG2, and production of IgG antibodies after vaccination with pneumococcal polysaccharides were also examined. ART-naive patients with HIV (n = 20) and controls (n = 20) were also assessed for comparison. Results: ART-treated patients had increased proportions of CD21 lo/- and tumor necrosis factor-related apoptosis-inducing ligand + B cells and, furthermore, although proportions of B and T lymphocyte attenuator + B cells were not significantly different from controls, they correlated negatively with CD21 lo/- B cells. Proportions of CD21 lo/- B cells also correlated negatively with current CD4 + T-cell counts. In ART-naive patients with HIV, free light chains correlated with CD21 lo/- B cells and IgG1, but not IgG2. Serum IgG2:IgG1 ratios were substantially lower than normal in patients with HIV and did not resolve on ART. In ART-treated patients, IgG antibody responses to pneumococcal polysaccharides after vaccination were not associated with markers of B-cell dysfunction. Conclusions: B-cell dysfunction persists in patients with HIV receiving long-term ART. The causes and consequences of this require further investigation. Abstract : Supplemental Digital Content is Available in the Text.